Performance of engineering graduates as perceived by employers: Past and present - Basri H.; Zaharim A.; Omar M.Z.; Yuzainee M.Y. (2023)
The objective of this paper is to observe the improvement of engineering graduates by comparing the employers' perception in the past and present, towards attributes owned by engineering graduates in their workplace. The data collected through face-to-face and telephone interviews with employers from Kelang Valley area of Malaysia in 2010 and from employers across sectors in various regions of Malaysia in 2006. The interviews were carried out only with high ranking officers, in this case; Head of Division or higher position to ensure accurate results. The employers responded to the level of satisfaction on each of the attributes performed by Malaysian graduates using Likert scale. The findings discovered that employers tend to rate engineering graduates better in 2010 than those in 2006. The result in 2010 indicates that there are 10 out of 13 attributes have a higher percentage of employers satisfied on the graduates' performance than to result in 2006. In 2010, the highest percentage (67.4%) of employers satisfied the performance of graduates on the ability to communicate effectively, not only with engineers but also with the community at large. However, in 2006, only 49.5% of employers satisfied the performance of graduates on this attribute. The attributes that obtained lower agreement on employers satisfaction in 2010 compared to those in 2006 are (1) ability to utilise a systems approach to design and evaluate operational performance, (2) ability to function effectively as an individual and in a group with the capacity to be a leader or manager as well as an effective team member and (3) having the knowledge of contemporary issues. 2012 IEEE.